2007
DOI: 10.1021/bm0608840
|View full text |Cite
|
Sign up to set email alerts
|

Novel Protein Fibers from Wheat Gluten

Abstract: Protein fibers with mechanical properties similar to those of wool and better than those of soyprotein and zein fibers have been produced from 100% wheat gluten. Wheat gluten is a low cost, abundantly available, and renewable resource suitable for fiber production. A simple production method has been developed to obtain high-quality wheat gluten fibers, and the structure and properties of the fibers have been studied. Wheat gluten fibers have breaking tenacity of about 115 MPa, breaking elongation of 23%, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
68
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 91 publications
(68 citation statements)
references
References 27 publications
0
68
0
Order By: Relevance
“…Previously, gliadin films were cast using ethanol as a solvent and to the best of our knowledge, no reports are available on using urea solutions as a solvent to make films from gliadin. However, urea solutions are routinely used to dissolve proteins and make fibers [7,8]. In the case of gliadin, it has been reported that high concentrations of urea can irreversibly transform the intramolecular disulfide bonds into intermolecular disulfide bonds.…”
Section: Effect Of Urea Concentrationmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, gliadin films were cast using ethanol as a solvent and to the best of our knowledge, no reports are available on using urea solutions as a solvent to make films from gliadin. However, urea solutions are routinely used to dissolve proteins and make fibers [7,8]. In the case of gliadin, it has been reported that high concentrations of urea can irreversibly transform the intramolecular disulfide bonds into intermolecular disulfide bonds.…”
Section: Effect Of Urea Concentrationmentioning
confidence: 99%
“…In addition to films, plant proteins have also been used to develop regenerated protein fibers for various applications [6][7][8][9]. However, films and fibers made from plant proteins have relatively poor mechanical properties and stability in water compared to similar materials made from synthetic polymers.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, efforts have been made since 1930s to produce regenerated protein fibers using various protein sources. Soyproteins, wheat gluten and gliadin, zein, keratin in feathers are some of the sources used to develop regenerated protein fibers [4][5][6]. Our group has demonstrated that byproducts such as soyprotein, zein, and wheat gluten obtained during processing of food grains for food and biofuels can be used to develop high quality regenerated protein fibers [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Soyproteins, wheat gluten and gliadin, zein, keratin in feathers are some of the sources used to develop regenerated protein fibers [4][5][6]. Our group has demonstrated that byproducts such as soyprotein, zein, and wheat gluten obtained during processing of food grains for food and biofuels can be used to develop high quality regenerated protein fibers [4][5][6]. The regenerated protein fibers developed from wheat gluten and soyproteins were crosslinked with carboxylic acids and reported to have properties similar to wool and suitable for textile and medical applications [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Although wheat based proteins, mainly gluten and gliadin, have been used for industrial applications such as fibers and films similar to soyproteins and zein, very few studies have been conducted on understanding the suitability of wheat proteins for medical applications [7][8][9][10][11][12][13]. Gliadin films were made into soft capsules and chewable gums for controlled drug release and it was reported that gliadin proteins showed high promise to be bioacceptable proteins with controlled release potency [14].…”
Section: Introductionmentioning
confidence: 99%